PRAKTEK KORUPTIF DALAM PENGADAAN BARANG DAN JASA PEMERINTAH - Rahmat Saputra (Universitas Bina Sarana Informatika, 2018)
The purpose of writing is to know the corrupt practices in the procurement of goods and services in terms of Law No. 20 of 2001 concerning Eradication of Corruption Crimes and prevention efforts. This type of research uses normative juridical approach. That corrupt practices in the procurement of goods and services is an action that we have often heard, so that it is not new anymore. Corruptive practices can exist because the interests of a group of parties who do not carry out the guidelines for the procurement of goods and services are not in accordance with procedures, in this case there is a need for prevention so that corrupt practices in procurement and services. The form of prevention is by improving in terms of regulation, in terms of implementing government procurement of goods and services in Indonesia, it is also improved by two ways; HR capacity building and the implementation of e-procurement and criminal law aspects in the relationship between the provider of goods and services procurement and users can be seen from the procurement preparation stage until the completion of the procurement of goods and services.